Current Status of Yellow Leaf Disease (YLD) of Sugarcane Caused by Sugarcane Yellow Leaf Virus (ScYLV) in the states of Andhra Pradesh and Telangana - Madugula, Suresh; Gali, Umadevi; Nalabolu, Raja Kumar; Merugu, Tirupathi (International Journal of Bio-resource and Stress Management, 2020)
Yellow Leaf Disease (YLD) of Sugarcane caused by Sugarcane Yellow Leaf Virus (ScYLV) is becoming a major threat to the sugarcane crop in the recent past. A survey was undertaken during 2012-13 to 2015-16 planting seasons in different sugarcane growing regions of Andhra Pradesh and Telangana states to assess the incidence levels and spread of Yellow Leaf Diseases (YLD) of sugarcane, a major threat to the crop in the recent past. A total of 521 fields covering 52 mandals in 8 districts of the states of Andhra Pradesh (2012-16) and Telangana (2013-14) were surveyed and kept under surveillance during different growth stages and the severity in both plant and ratoon fields was recorded. The mean YLD incidence ranged between 10 to 56.5%, with increased incidence being observed in ratoon fields (15-74.5%) compared to plant fields (5-38.5%). Further, Telangana region recorded higher incidence levels than Andhra Pradesh region. The study indicated that, replacement of varieties and planting material in sugar factory areas resulted in decreased incidence of YLD during 2014-15 and 2015-16 seasons with a mean incidence pegged at 26.3%. The YLD incidence and disease grades were mapped using GPS information of the surveyed areas in collaboration with CRIDA, Hyderabad. The GIS based mapping clearly showed the distribution and progress of the disease in different districts of AP and Telangana states over the study period.